Household Livelihood and Coping Strategies of Nomads in Northeastern Nigeria (2016)
The changing climate heightens drought situations especially in Northern Nigeria and induces multiple stresses on nomads and their animals. Resulting water and pasture insufficiency impose hardship on their livelihood. Little is known about coping strategies adopted for their stressed livelihood. Therefore, household livelihood and coping strategies of nomads in Northeastern Nigeria were investigated. A four-stage sampling procedure was used to select respondents for the study. Three states (Adamawa, Taraba and Bauchi) were randomly selected from the six states in the study area. From these states, 15% of Local Government Areas (three, two, and three, respectively) were randomly selected, while five communities and 10 respondents were randomly selected from each, giving a total of 400 respondents. Interview schedule and Focus Group Discussion (FGD) were used to collect data on respondents’ socioeconomic characteristics, coping strategies (low: 1.00-12.20; high: 12.21-38.00)], perception of the effects of drought (unfavourable: 40.00-95.91; favourable: 95.92-118.00), challenges to livelihood and livelihood status: (low: 0.00-3.61; high: 3.62-11.65). Livelihood status was made up of access to capital assets, livelihood activities in the dry season (low: 0.00-26.16; high: 26.17-122.00) and rainy season (low: 0.00-23.90; high: 23.91- 81.00) and household capabilities (low: 5.00-25.17; high: 25.18-83.00). Capital assets include: human/social (low: 0.00-5.61; high: 5.62-47.00), natural (low: 0.00-5.59; high: 5.60-8.00), physical (low: 0.00-6.89; high: 6.90-15.00) and financial (low: 0.00-1.32; high: 1.33-6.00). Data were analysed using descriptive statistics, Pearson’s product moment correlation, multiple linear regression and ANOVA at α 0.05. Most respondents were married (91.1%), below 56 years (84.0%), male (90.8%) with one wife (62.6%), children (6.0±3.99) and dependents (3.0±1.60). Majority (81.3%) had no formal education and was primarily engaged in animal husbandry (77.7%) with monthly income of N15, 000 (I.Q.R.: N37, 000). Majority (65.6%) of the respondents had low access to human/social capital, 60.7% had high access to natural capital, 59.5% had high access to physical capital and 75.2% had low access to financial capital. Many (55.8%) had low use of livelihood activities in dry season, high use (23.91-81.00) in the rainy season (59.5%) and low household capability (62.3%). Many respondents had low coping strategies (63.5%) and favourable perception of the effects of drought on their livelihood (52.1%). Most (82.6%) noticed major alterations in rainfall patterns with hunger (58.6%) and poverty (57.6%) being consequent impacts. Other challenges to livelihood included migration for drought related problems (70%), lack of rainfall (45.0%) and drying up of lakes and streams (35.9%). The FGD revealed that terrorist activities led to disruption of respondents’ social and cultural activities and loss of livelihoods as well as death of many nomadic household members. Livelihood status significantly correlated with monthly income from primary occupation (r=0.23) and number of total coping strategies used (r=0.631). Significant difference existed in respondents’ coping strategies and livelihood status across states. Respondents’ age (β=-0.29), number of sources of income (β=0.20), number of secondary occupation (β=-0.26), perception (β=0.18) and number of coping strategies used (β=0.33) contributed significantly to livelihood status. Livelihood status and use of coping strategies of nomads in Northeastern Nigeria were low.